Understanding Teacher Accompaniment in Schools: The Development and Validation of the Teacher Accompaniment Scale - Baring, Rito (Animo Repository, 2020)
In the present study, we examined the psychometric properties of the Teacher Accompaniment Scale (TAS) for senior high and college students from eight schools in Manila. We investigated the empirical basis to develop a reliable measure that assesses student attitudes towards teacher accompaniment. Participants included 1,618 Grade 12 senior high students and college students from selected public and private schools. The study design included exploratory factor analysis for data reduction and confirmatory factor analysis to examine the best fit model. The results showed two dimensions assessing teachers as sources of support and stress. In response to the limited scholarship on teacher accompaniment in the country, the present work provides an empirical characterization of teacher behavior and personality in class using latent dimensions. Second, the development of TAS is a modest contribution to map out articulations of teacher accompaniment in the ASEAN region. Third, this work raises the inclusion of teacher personality and behavior as an arguable point in assessing teacher effectiveness side by side teaching strategies, methods, and competence. Analysis of the results is examined with respect to university teaching practices and implications for student learning.